Efficient and reliable surface charge transfer doping of black phosphorus via atomic layer deposited MgO toward high performance complementary circuits. Issue 36 (11th September 2018) - Liao, Wugang; Wang, Lin; Chen, Li; Wei, Wei; Zeng, Zhe; Feng, Xuewei; Huang, Li; Tan, Wee Chong; Huang, Xin; Ang, Kah Wee; Zhu, Chunxiang
Abstract : Efficient n-doping for BP transistors is realized via atomic layer deposited MgO for the implementation of high-performance complementary logic inverters. Abstract : Black phosphorus (BP), a fast emerging 2D material, has shown great potential in future electronics and optoelectronics owing to its outstanding properties including sizable band gap and ambipolar transport characteristics. However, its hole conduction dominance, featured by a much larger hole mobility and the corresponding on-current than that of the electrons, renders the reliable modulation of its carrier type and density a key challenge, thereby hindering its application to complementary electronics. Here, we demonstrate an efficient and reliable n-type doping for BP transistors via surface functionalization by atomic layer deposited magnesium oxide (MgO) with favorable controllability. By optimizing the MgO thickness, an electron mobility of up to 95.5 cm 2 V −1 s −1 is reached with a simultaneous significant suppression of hole conduction. Subsequently, a high-performance complementary logic inverter is demonstrated within a single BP flake, which operates well with a supply voltage as low as <0.5 V, outperforming reported BP inverters in terms of logic level match, power consumption and process feasibility. Our findings suggest that surface charge transfer doping via MgO can be used as a promising technique towards high performance BP-based functional nanoelectronics.